Endosomal PI(3)P regulation by the COMMD/CCDC22/CCDC93 (CCC) complex controls membrane protein recycling - Amika Singla (Nature Portfolio, 2019)
Recycling of proteins that have entered the endosome is essential to homeostasis. The COMMD/CCDC22/CCDC93 (CCC) complex is regulator of recycling but the molecular mechanisms are unclear. Here, the authors report that the CCC complex regulates endosomal recycling by maintaining PI3P levels on endosomal membranes.